-(h+7)=8h

Simple and best practice solution for -(h+7)=8h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(h+7)=8h equation:


Simplifying
-1(h + 7) = 8h

Reorder the terms:
-1(7 + h) = 8h
(7 * -1 + h * -1) = 8h
(-7 + -1h) = 8h

Solving
-7 + -1h = 8h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-8h' to each side of the equation.
-7 + -1h + -8h = 8h + -8h

Combine like terms: -1h + -8h = -9h
-7 + -9h = 8h + -8h

Combine like terms: 8h + -8h = 0
-7 + -9h = 0

Add '7' to each side of the equation.
-7 + 7 + -9h = 0 + 7

Combine like terms: -7 + 7 = 0
0 + -9h = 0 + 7
-9h = 0 + 7

Combine like terms: 0 + 7 = 7
-9h = 7

Divide each side by '-9'.
h = -0.7777777778

Simplifying
h = -0.7777777778

See similar equations:

| 460=3x+x | | 15=x-(-2) | | 10=8-3x | | -10-k=-16 | | 460=3x+y | | 10=8-3 | | x^3+2x+x=0 | | -10+n=-17 | | X/3/4 | | 51x-55=47 | | (2/7)/(5/9) | | 40x^2+84x+56=0 | | (3-2x-x^2)/(x^2-1) | | 18k^2-103k+119=0 | | (5/3)*(5/8) | | 5/3*5/8 | | 9-p=6 | | 10x-8=10x | | 2x=1/2*(x+4y+2z) | | 19x^2+36x-4=0 | | 6-9x=105-30x | | 3x+12=x+72 | | x+3x+5x-6=180 | | 3a-8a=11a | | x^5y^4/x^3y^6 | | 3n^2-16n+21=0 | | a/15+5=4 | | -40-9x=214-44x | | 1150+15x=y | | x+2+3x=57 | | 66-22x=3x+6 | | 10(x+12)=-70 |

Equations solver categories